Analysis Of Leadership And Organizational Commitment On Employee Performance With Satisfaction As A Mediating Variable In Medan Tuntungan District Office - Yanta, Nesron; Rahayu, Sri; Ritonga, Husni Muharram (Journal of Management, Economic, and Accounting, 2026)
Employee performance is a key factor in determining the quality of public services in government agencies, including the Medan Tuntungan Sub-District Office. Differences in work quality, timeliness of task completion, and employee initiative levels indicate that employee performance is not yet fully optimal. This study aims to analyze the influence of leadership and organizational commitment on employee performance with job satisfaction as a mediating variable at the Medan Tuntungan Sub-District Office. This study uses a quantitative approach with a survey method. The population in this study was all 67 civil servants (PNS) at the Medan Tuntungan Sub-District Office, with a sampling technique using the census method. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method with the help of SmartPLS software. The results showed that leadership and organizational commitment had a positive and significant effect on employee performance and job satisfaction. Job satisfaction also has a positive and significant effect on employee performance. In addition, job satisfaction has been proven to play a significant mediating role in the relationship between leadership and organizational commitment to employee performance. These findings indicate that improved employee performance can be achieved through strengthening effective leadership, increasing organizational commitment, and creating better job satisfaction to support improved quality of public services